Portfolio performance evaluation of mutual funds in the Republic of Serbia - Leković, Miljan; Jakšić, Milena; Gnjatović, Dragana (Serbian Journal of Management, 2020)
The paper evaluates the performance of open-end mutual funds in the Republic of Serbia in the period 2011-2015, using various modelling approaches based on different models. The aim of this paper is to examine the theoretical, methodological and empirical validity of active portfolio management of mutual funds and to assess the presence of selection and timing abilities of Serbian portfolio managers. The results of the empirical research show that the active portfolio management of mutual funds in the Republic of Serbia has not been successful in terms of outperforming the market. Portfolio managers of most Serbian mutual funds lack the ability to choose profitable securities and do not have market timing ability.
Keywords: mutual funds; performance evaluation; selection ability; market timing ability